The Effect of Self-Regulated Learning Toward Student’s Writing Ability - Khasanah, Shokhikhatul; Kiswati, Kiswati; Muslim, Abd Hakim (CV. Edutechnium Indonesia, 2024)
Students need Self-Regulated Learning (SRL) to understand mistakes in scientific writing and achieve conceptual understanding. Background knowledge, age, gender, motivation, and self-regulated learning are affective factors that influence a person's success in acquiring a second language. For this reason, researchers then took self-regulated learning as a moderating variable in this study. The objective of this research is to determine whether there are differences in English writing abilities between students with different self-regulated learning. This study implemented a flipped classroom, while self-regulated learning was the moderator variable. The research method used in this study is a quasi-research with a pre-test and post-test control group design, while the teaching method for the experimental group used a flipped classroom. The participants of this study were 89 students. The study found differences in students' ability to write English based on SLR (Self-regulated learning). Future researchers are recommended to combine Self-Regulated Learning with other independent variables to obtain more diverse and useful data in educational research.